Information sampling and adaptive cognition - Fiedler, Klaus; Juslin, Peter (Cambridge Univ. Press, 2006)
Taking the interface between mind and environment seriously / Klaus Fiedler and Peter Juslin -- Good sampling, distorted views : the perception of variability / Yaaov Kareev -- Intuitive judgments about sample size / Peter Sedlmeier -- The role of information sampling in risky choice / Ralph Hertwig ... [et al.] -- Less is more in covariation detection - or is it? / Peter Juslin, Klaus Fiedler, and Nick Chater -- Subjective validity judgments as an index of sensitivity to sampling bias / Peter Freytag and Klaus Fiedler -- An analysis of structural availability biases, and a brief study / Robyn M. Dawes -- Subjective confidence and the sampling of knowledge / Joshua Klayman ... [et al.] -- Contingency learning and biased group impressions / Thorsten Meiser -- Mental mechanisms : speculations on human causal learning and reasoning / Nick Chater and Mike Oaksford -- What's in a sample? A manual for building cognitive theories / Gerg Gigerenzer -- Assessing evidential support in uncertain environments / Chris M. White and Derek J. Koehler -- Information sampling in group decision making : sampling biases and their consequences / Andreas Mojzisch and Stefan Schulz-Hardt -- Confidence in aggregation of opinions from multiple sources / David V. Budescu -- Self as sample / Joachim I. Krueger, Melissa Acevedo, and Jordan M. Robbins -- Which world should be represented in representative design? / Ulrich Hoffrage and Ralph Hertwig -- "I'm m/n confident that I'm correct" : confidence in foresight and hindsight as a sampling probability / Anders Winman and Peter Juslin -- Natural sampling of stimuli in (artificial) grammar learning / Fenna H. Poletiek -- Is confidence in decisions related to feedback? Evidence from random samples of real-world behavior / Robin M. Hogarth
Literaturangaben
Keywords: Aufsatzsammlung; Informationsverarbeitung; Entscheidungsfindung; Kognition; Kommunikation